Fully Revised Estimates of Principal Crops in Karnataka for the Year 1990-91 Government of Karnataka - Planning Commission (Planning Commission, 1993)
This publication embodies the final tables on area, production and average yield of principal crops grown in Karnataka during the year 1990-91. the area estimates are based on Annual season and Crop Reports received from the Tahsildars through the District Statistical Officers. the results of the crop estimation survey 1990-91 wherever available, have been used in building up the production estimates. From the year 1990-91, area, production and productivity of major cereal crops and groundnut are given for irrigated and unirrigated areas separately.
Directorate of Economics and Statistics, Bangalore
Directorate of Economics and Statistics, Bangalore